Cost Efficiency Analysis of Oyster Mushroom Baglogs’ Raw Material Inventory in CV. DA - Jannah, Lu'lu'ul; Yuswita, Effy; Riana, Fitria Dina (Interdisciplinary Social Studies, 2023)
Background: Oyster mushrooms are famous for having many benefits, in addition to being used as a nutrient-filled food ingredient can also be trusted since a long time ago as a traditional medicine. Aim: This study aims to describe the inventory control carried out for baglog raw materials, analyze the optimal baglog raw material inventory costs using the JIT and EOQ methods, determine the efficiency of inventory costs and recommend more appropriate methods and purchasing quantities. Method: This study uses the JIT and EOQ methods for data analysis. Findings: The results showed that the control of baglog raw material inventory still uses conventional methods, the company determines the quantity of raw material purchases by doing a breakdown. The optimal baglog raw material inventory cost using the EOQ method is Rp 6.055.453, when using the JIT method, it is Rp 5.185.075. Inventory cost efficiency using the JIT method is 29%, when using the EOQ method, the inventory cost efficiency is 17%. The recommended method given is the JIT method because it is more efficient and has been adapted to the company's conditions.